2020
DOI: 10.7759/cureus.7084
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Surgical Approach to Intradural Spinal Tumors: Laminectomy or Hemilaminectomy?

Abstract: Traditionally, laminectomy has been the preferred surgical approach for the resection of intradural spinal tumors. Recent trends towards minimally invasive techniques have generated interest in hemilaminectomy as an effective alternative surgical approach to resect spinal tumors. However, it remains unclear if the potential benefits of hemilaminectomies, used in other routine spinal procedures, apply to intradural spinal tumors. This report presents a sixyear single institutional analysis of open resection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Ultimately, the approach will depend on the type and localization of the tumor and the surgeon's ability to handle nerves and resect bones. A minimally invasive approach can always be helpful for patients if tumor removal can be performed safely and reliably [ 2 , 4 , 9 ]. Several reports compared spinal cord tumor removal techniques, but none of them clearly describes the appropriate site and level of indication for laminectomy or laminoplasty [ 2 - 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the approach will depend on the type and localization of the tumor and the surgeon's ability to handle nerves and resect bones. A minimally invasive approach can always be helpful for patients if tumor removal can be performed safely and reliably [ 2 , 4 , 9 ]. Several reports compared spinal cord tumor removal techniques, but none of them clearly describes the appropriate site and level of indication for laminectomy or laminoplasty [ 2 - 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A minimally invasive approach can always be helpful for patients if tumor removal can be performed safely and reliably [ 2 , 4 , 9 ]. Several reports compared spinal cord tumor removal techniques, but none of them clearly describes the appropriate site and level of indication for laminectomy or laminoplasty [ 2 - 4 , 10 ]. The introduced system is highly useful in terms of versatility because we can plan various surgical techniques [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7] In accordance, the study by Caroli et Management of spinal IDEM tumors is tumor resection surgery in generally. [10] A retrospective study suggested a significant improvement in neurological deficit posttumor resection on patients with spinal IDEM tumor, regardless of the percentage of tumors occupying the intradural space, the degree of preoperative symptoms, and the duration of symptoms. [9] Study by Goodarzi et al suggested that there was no significant difference in the length of operation, estimated blood loss, or in the length of hospital stays between the spinal IDEM tumor's approaches of laminectomy or hemilaminectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[3], [7] Management of spinal IDEM tumors is tumor resection surgery but biopsy is the only method to definitively confirm diagnosis through tumor resection surgery. [8], [9], [10] The pathognomonic histologic feature of a meningioma is spherical formations of meningothelial cells, called whorls, which eventually mineralize into psammoma bodies. A range of histologic patterns and findings can be seen that often mimic other soft tissue tumors, as indicated by the numerous variants just among benign grade I tumors: meningothelial, fibrous, transitional, psammomatous, angiomatous, microcystic, secretorym, lymphoplasmacyte-rich and metaplastic.…”
Section: Introductionmentioning
confidence: 99%
“…Different surgical techniques are used for excision of IDEM spinal tumors. Laminectomy has been the classic approach and also hemilaminectomy and they are still used for that despite the development of minimally invasive technique that aim to avoid potential complication of the classic approach, the laminectomy allows for better exposure, convenient work, and continue to be the preferred method for resection of large tumors with complex morphology (9) .…”
Section: Introductionmentioning
confidence: 99%